2015
DOI: 10.4236/asm.2015.54009
|View full text |Cite
|
Sign up to set email alerts
|

Association between Early Marriage and Other Sociomedical Characteristics with the Cervical Pap Smear Results in Iraqi Women

Abstract: Background: The standard screening test for cervical cancer is the Pap smear and cervical cancer is a significant health issue worldwide. Early sexual activity, multiple sexual partnerships, parity, young age at first pregnancy and early marriage are traditional risk factors for developing cervical cancer. The aim of the present study was to assess the effect of early marriage in on the results of Pap smear in Iraqi women. Methods: A cross-sectional study was carried out on 200 women who attended the Women Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
1
9
1
Order By: Relevance
“…In our study, the majority of the subjects (>50%) were in the age group of 41-61 years (Fig.1). A study performed in2010 reported a low prevalence of HPV in the young women and general populationwhich is in line with the findings of our study [25,26]. Though, HPV types 16/18 did not have a significant pattern in age-specific distribution (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, the majority of the subjects (>50%) were in the age group of 41-61 years (Fig.1). A study performed in2010 reported a low prevalence of HPV in the young women and general populationwhich is in line with the findings of our study [25,26]. Though, HPV types 16/18 did not have a significant pattern in age-specific distribution (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Various small-scale local studies from India presenting HPV 16/18 type distribution in association with cervical cancer have been carried out [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Not a single study has been carried out in Bihar for HPV prevalence in cervical cancer patients where the 88.7% population resides in rural India.…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings have been published by other studies conducted by Khalaf MK et al (70.5%), Zainab et al (51.92%), Tapasvi I et al (92.3%). [15][16][17] Early marriages, leads to longer sexual life and being sexually active for longer duration elevates the number of pregnancies, abortions, deliveries and increases the chances of sexually transmitted infection. HPV is a very common sexually transmitted infection worldwide and its infection has been found in almost all cases of invasive cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The time from infection to the development of invasive cancer is thought to be many years; typically between 10 and 40. 6,11,13,15,18,19 Marriage at younger age then leads to longer sexual life which proves to be a significant risk factor in cervical dysplasia and also increases susceptibility of adolescent cervix to oncogenic irritation. The adolescent cervix is vulnerable to various potential oncogenic factors (HPV) when exposed and results in increase incidence of dysplasia and its further course.…”
Section: Discussionmentioning
confidence: 99%
“…Based on other studies, women who married at age ≤ 20 years are five times more likely to develop cervical cancer (Setyarini, 2012). Moreover, in the study of Iraqi women indicated that very young married age is strongly associated with abnormal pap smear examination results (Khalaf, Rasheed, & Hussain, 2015). Variable types of contraception with exp (β) = 488.484 explains that patients using hormonal contraception devices will be at risk of cervical cancer by 488.484 times greater than patients who use non hormonal contraception.…”
Section: Ijphcsmentioning
confidence: 99%